KEWENANGAN PENGADILAN AGAMA DALAM HAL PEMBAGIAN WARIS BEDA AGAMA MELALUI WASIAT WAJIBAH (STUDI PENETAPAN PENGADILAN AGAMA JAKARTA SELATAN NOMOR 890/PDT.P/2021/PA.JS) - Nabila, Putri; Azheri, Busyra; Mannas, Yussy Adelina (Universitas Ekasakti, 2023)
Inheritance law is the law that regulates the transfer of ownership rights over the inheritance of the heir, then determines who is entitled to become the heir and how much is each part. Regarding the inheritance rights of non-Muslims, the Compilation of Islamic Law refers more to the opinions of scholars who assert that there are religious differences between heirs with heirs that become a barrier to inheritance. In terms of determining the distribution of heirs of different religions, the Religious Courts play a role in upholding justice, truth, order, and legal certainty regarding Islamic civil cases. In 2021 the South Jakarta Religious Court issued stipulation number 890/Pdt..P/2021/PA.JS in which in this decision the South Jakarta Religious Court granted the request for determination of heirs and distribution of legal inheritance from parents who entered into an interfaith marriage with the initials ISW (hereinafter referred to as a first child) who is non-Muslim, and gets a mandatory will of 1/3 of S's inheritance and does not exceed this provision. The formulation of the problems in this research are: 1) What are the judges' considerations in granting the request for determination of heirs and distribution of inheritance in the South Jakarta Religious Court's Decision Number: 890/Pdt.P/2021/PA.JS? 2) How is the division of inheritance from interfaith marriages? This study uses a normative juridical method which is an approach through the practice of law enforcement against laws that are written and equipped with existing legal documents in Indonesia. The results of this study are 1) The basis for the judge's consideration in the Determination of the South Jakarta Religious Court Number: 890/Pdt.P/2021/PA.JS is based on applicable law and the facts revealed in the trial. 2) Distribution of inheritance from interfaith marriages to realize justice and benefit, namely non-Muslim heirs are entitled to inheritance in the form of a mandatory testament.